Understanding the millennials’ customer experience in hospitality throughout the customer journey - Neves, Mafalda de Andrade Segurão Cardoso (2022)
The importance of experiences as a way of gaining competitive advantage highlighted the need to study them especially in the hospitality and tourism sector, as an area with specific characteristics that make these experiences difficult to predict. In particular, the experiences of millennials are of great importance, due to their weight of global travel, significant economic contribution and particularities that shape the industry. Thus, this dissertation aims to study the experiences of millennials along the journey in hotels, through the customer journey mapping in order to have a clear view of the interactions between this generation and these establishments. The results revealed heterogeneity in the journey of millennials in hotels according to the traveler type, resulting in distinct maps. Overall, the interactions identified were, before the experience, the research, comparison and booking, during the experience, the check-in, room, meals included, restaurant, bar, pool, gym, entertainment, and check-out, and after the experience, the evaluation and promotions. In each map, it was concluded that the actions, channels, feelings, expectations, points of delight and pain points vary throughout the journey and recommendations were identified to improve the service at each stage. The study of the customer experience in hotels constitutes a contribution to the theory through the use of customer journey mapping, which, in this context, has received limited attention in the literature. By mapping the millennials’ journey, hotels are able to identify the opportunities and weaknesses associated with their services and understand how they can adapt them to captivate this generation.